2009
DOI: 10.1177/0022487109341150
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Work of Leading Mathematical Tasks in Professional Development

Abstract: Filling the knowledge gap in the limited research on professional development leaders is an urgent issue if teacher learning is to be improved. This research and development project is studying how leaders learn to cultivate mathematically rich professional development environments. The authors adapted two frameworks from classroom-based research-sociomathematical norms and practices for orchestrating productive discussion-to support leaders' understanding of facilitation of mathematics professional developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 22 publications
2
79
0
16
Order By: Relevance
“…Other research found that teachers were more likely to change their instructional practice when participating in PD programs that offered ongoing on-site support and teacher networks that could work collaboratively within and across schools and districts (Corcoran, McVay, and Riordan, 2003). This is consistent with a larger body of scholarly work suggesting that effective PD is sustained and intensive (Marrongelle, Sztajn, and Smith, 2013;Loveless, 2013) and involves collective participation and group work (Desimone, 2009;Elmore, 2002;Guskey and Yoon, 2009;Wei et al, 2009;Elliott et al, 2009).…”
Section: Administrator and Teacher Professional Developmentmentioning
confidence: 75%
“…Other research found that teachers were more likely to change their instructional practice when participating in PD programs that offered ongoing on-site support and teacher networks that could work collaboratively within and across schools and districts (Corcoran, McVay, and Riordan, 2003). This is consistent with a larger body of scholarly work suggesting that effective PD is sustained and intensive (Marrongelle, Sztajn, and Smith, 2013;Loveless, 2013) and involves collective participation and group work (Desimone, 2009;Elmore, 2002;Guskey and Yoon, 2009;Wei et al, 2009;Elliott et al, 2009).…”
Section: Administrator and Teacher Professional Developmentmentioning
confidence: 75%
“…In particular, the Leader Project was designed to enhance leaders' ability to facilitate mathematically rich learning opportunities for teachers (Elliott, Kazemi, Lesseig, Mumme, Carroll, & Kelley-Petersen, 2009). Data for this paper comes from phase II of the project, which involved thirty-five teacher-leaders, (i.e.…”
Section: Methods Participants and Contextmentioning
confidence: 99%
“…Researchers have recently enlisted two frameworks to guide the study of facilitation in mathematics professional development-framing facilitation in terms of attention to sociomathematical norms (Elliott et al, 2009;Yackel & Cobb, 1996) and the orchestration of productive discussions (Borko, Jacobs, Seago, & Mangram, in press;Elliott et al, 2009;Stein, Engle, Smith, & Hughes, 2008). Both these frameworks were initially developed in the context of mathematics classroom learning and teaching and both are grounded in a situative perspective.…”
Section: Using the Situative Perspective To Explore Facilitation Of Mmentioning
confidence: 99%